Lobo Mau!? Uma análise pela teoria do imaginário - Colla, Laura Ferrari (My University, 2025)
This study aims to analyze the representations of the Big Bad Wolf in contemporarychildren's stories. The research is bibliographic in nature, employing a literature review combined with analytical methods, using articles, dissertations, books, and multimedia resources relevant to the subject of study. To this end, the first chapter is divided into two subsections: the first addresses the various representations of the wolf in different mythologies and children's narratives; subsequently, a brief historical overview is presented on the importance of children's literature and the use of fantasy for young audiences. This initial part draws on concepts from Marisa Lajolo, Regina Zilberman, Michael Levy, and Farah Mendlesohn. The following chapter explores the concepts of the unconscious and the imaginary through a group of authors, such as Gaston Bachelard, Marie-Louise von Franz, Joseph Campbell, Gilbert Durand, Michel Maffesoli, and Juremir Machado. Some multimedia works are also examined as examples in which the wolf is portrayed differently from the versions by the Brothers Grimm and Charles Perrault. The third chapter presents, in more detail, the selected works to be analyzed through the lens of the theory of the imaginary, the works are: Yellow Riding Hood (1979), by Chico Buarque; The True Story of the Three Little Pigs (1989), written by Jon Scieszka; The True Story of Little Red Riding Hood (2007), by Agnese Baruzzi; and finally, The Wolf's Hunger (2012), by the author Maria Claudia Vasconcelos, are some of the works that revisit classic fairy tales through new narrative perspectives. Finally, the conclusion presents the findings resulting from the analysis and reading of the works. It is especially noted that, despite the different representations, the wolf is still understood as a symbol of evil, and that its instincts prevail over its ability to change its behavior. [resumo fornecido pelo autor]
O presente trabalho tem como objetivo principal analisar as representações do lobo mau em histórias infantis contemporâneas. A pesquisa se caracteriza comobibliográfica, tendo como método um levantamento de artigos, dissertações, livros e recursos multimídia pertinentes ao objeto de estudo, apresentando posterior análise, do ponto de vista da teoria do imaginário, da figura do lobo. Para esse fim, o primeiro capítulo se divide em duas subseções: a primeira aborda as representações do lobo em diferentes mitologias e narrativas infantis; a seguir, traça-se, de forma breve, o percurso histórico da literatura infantil e discute-se o papel da fantasia. Nessa parte inicial, são utilizados conceitos de Marisa Lajolo, Regina Zilberman, Michael Levy e Farah Mendlesohn. No capítulo seguinte, são abordados os conceitos de inconsciente e de imaginário para Gaston Bachelard, Marie-Louise von Franz, Joseph Campbell, Gilbert Durand, Michel Maffesoli e Juremir Machado da Silva. Ainda são abordadas algumas obras multimídias - a título de exemplo, em que o lobo foi representado de forma divergente às narrativas dos irmãos Grimm e de Charles Perrault. No terceiro capítulo são apresentadas, de forma estendida, as obras a serem analisadas pela teoria do imaginário. São elas: Chapeuzinho Amarelo (1979), de Chico Buarque; A verdadeira História dos Três Porquinhos (1989), escrita por Jon Scieszka; A Verdadeira História de Chapeuzinho Vermelho (2007), de Agnese Baruzzi; e para finalizar, A Fome do Lobo (2012), da escritora Maria Claudia Vasconcelos. Por fim, a conclusão apresenta os resultados obtidos a partir da análise das obras. Destaca-se especialmente que, apesar das diferentes representações, o lobo ainda é entendido como símbolo de maldade e que seus instintos são superiores à sua capacidade de alterar seu comportamento. [resumo fornecido pelo autor]
Keywords: Personagens literários; Literatura infantil - Crítica e interpretação; Imaginação em crianças; Simbolismo na literatura; Characters and characteristics in literature; Children's literature - Criticism and interpretation; Imagination in children; Symbolism in literature